Mnemonic legality: militarism, masculinity, and the elasticity of belonging. Issue 1 (2nd January 2019) - Howard, Matt
ABSTRACT: This paper adopts the idea that nationally observed commemorative events are pivotal in the enactment of identity. Exemplified by Anzac Day, collective mnemonic narratives are implicated in the process of producing particular conceptions of what is normative and valued within a legal and political community. The notion of collective memory's contribution to the production of normative and formative frames, and associated senses of belonging and recognition, is brought into conversation with the theorisation of the plurality of law. Interview data from a project examining the experiences of expatriate homosexual Australian men is introduced in order to explore the entanglement of Anzac Day commemoration and law in the elastic quality of normative frames to tolerate difference while also being inherently exclusionary.